2017
DOI: 10.4102/sajhrm.v15i0.880
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing managers’ attitudes towards performance appraisal

Abstract: Orientation: Managers often have negative attitudes towards performance appraisal because of its problematic nature, which is influenced by political and social contextual factors. These negative attitudes lead to reduced employee support, inaccurate performance appraisal ratings and, consequently, negative employee perceptions of the performance appraisal process. This state of affairs necessitates a deeper understanding of the factors influencing managers’ attitudes towards performance appraisal.Research pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…It was also found that tension manifests itself when managers feel threatened by evaluation (Siverbo et al , 2019), or uncomfortable and defensive because they have to evaluate their subordinates, which could affect their relationships (Du Plessis and Van Niekerk, 2017). In other words, a feeling of tension is manifested both because managers are evaluated and because they evaluate their subordinates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also found that tension manifests itself when managers feel threatened by evaluation (Siverbo et al , 2019), or uncomfortable and defensive because they have to evaluate their subordinates, which could affect their relationships (Du Plessis and Van Niekerk, 2017). In other words, a feeling of tension is manifested both because managers are evaluated and because they evaluate their subordinates.…”
Section: Resultsmentioning
confidence: 99%
“…This analysis is relevant to groups with different interests, since the way in which each organisation member is affected differs on their different functions (Franco-Santos et al , 2012). Individual intentions must also be considered when analysing UCs (Du Plessis and Van Niekerk, 2017). That is, even if the consequences are unintentional from an organisational point of view, they can be intentional from the individual point of view, which is the case of conscious consequences.…”
Section: Final Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this aspect may rather fall into one of the extrinsic motivation categories. It has been shown that a more positive attitude towards the pay-setting system may increase managers' motivation to work with the pay setting (Du Plessis & van Niekerk, 2017). Based on the AMO framework, we argue that higher motivation leads to higher enacted justice in pay setting.…”
Section: The Role Of Motivationmentioning
confidence: 86%
“…Despite their now widely spread use in Canadian universities, deans' reappointments POLITICAL BEHAVIOUR IN DEANS' REAPPOINTMENTS 4 have eluded research efforts to this point. Furthermore, research on performance appraisals, a field closely related to reappointments, has provided evidence of political interference in both employees' (Du Plessis & Van Niekerk, 2017;Longenecker, Sims, & Gioia, 1987;Rosen, Kacmar, Harris, Gavin, & Hochwarter, 2017;Swanepoel, Botha, & Mangonyane, 2014) and managers' (Gioia & Longenecker, 1994;Kanyangale & Zvarevashe, 2013;Longenecker, 1997) evaluations, confirming that raters' goals often shape their ratings to a greater extent than ratees' performance (Murphy, 2008;Murphy, Cleveland, Skattebo, & Kinney, 2004;Smith, Craig Wallace, & Jordan, 2016).…”
Section: Purposementioning
confidence: 96%